Threshold gain analysis in GaN-based photonic crystal surface emitting lasers - Weng, Peng-Hsiang; Wu, Tzeng-Tsong; Lu, Tien-Chang; Wang, Shing-Chung (My University, 2011)
We have analyzed threshold gains and lasing modes in GaN-based photonic crystal (PC) surface emitting lasers (PCSELs) by using the multiple scattering method (MSM) for triangular-lattice PC patterns. Moreover, GaN-based PCSELs with different boundary shapes have been fabricated and measured. The lasing mode at the G band edge of GaN-based PCSELs can be identified by using the angled resolved spectroscopy and matched well to the results calculated by MSM. Threshold conditions in the GaN-based PCSELs with different boundary shapes are obtained by optical pumping and agree well with simulation results. (C) 2011 Optical Society of America